Supply chain analytics implementation: A TOE perspective - Sebastian Lodemann; Wolfgang Kersten (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: Increasing quantity and sources of data and their potential to fuel value-adding applications in Supply Chain Management (SCM) are of considerable importance for corporations. Methodology: We utilize a qualitative research design of semi-structured expert interviews. Findings: Utilizing the Technology-Organization-Environment framework, we establish an integrated perspective: We propose that CSF possess a varying relevance to the success of the SCA (Supply Chain Analytics) project, depending on the initial drivers. Originality: While the benefit and potential value of SCA is established, the implementation of the technology remains a challenge for companies. This paper combines the concept of 'drivers' for adoption with Critical Success Factors (CSF) during the initial implementation.
urn:nbn:de:gbv:830-882.0161889; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; Business Analytics